Resection versus biopsy in patients with glioblastoma (RESBIOP study): study protocol for an international multicentre prospective cohort study (ENCRAM 2202) - Gerritsen, Jasper; Young, Jacob S.; Krieg, Sandro; Jungk, Christine; Ille, Sebastian; Schucht, Philippe; Nahed, Brian V.; Broekman, Marike Lianne Daphne; Berger, Mitchel; Vleeschouwer, Steven De; Vincent, Arnaud J. P. E. (BMJ open, 2024)
Introduction There are no guidelines or prospective studies defining the optimal surgical treatment for glioblastomas in older patients (≥70 years), for those with a limited functioning performance at presentation (Karnofsky Performance Scale ≤70) or for those with tumours in certain locations (midline, multifocal). Therefore, the decision between resection and biopsy is varied, among neurosurgeons internationally and at times even within an institution. This study aims to compare the effects of maximal tumour resection versus tissue biopsy on survival, functional, neurological and quality of life outcomes in these patient subgroups. Furthermore, it evaluates which modality would maximise the potential to undergo adjuvant treatment. - Methods and analysis This study is an international, multicentre, prospective, two-arm cohort study of an observational nature. Consecutive patients with glioblastoma will be treated with resection or biopsy and matched with a 1:1 ratio. Primary endpoints are (1) overall survival and (2) proportion of patients that have received adjuvant treatment with chemotherapy and radiotherapy. Secondary endpoints are (1) proportion of patients with National Institute of Health Stroke Scale deterioration at 6 weeks, 3 months and 6 months after surgery; (2) progression-free survival (PFS); (3) quality of life at 6 weeks, 3 months and 6 months after surgery and (4) frequency and severity of serious adverse events. The total duration of the study is 5 years. Patient inclusion is 4 years; follow-up is 1 year. - Ethics and dissemination The study has been approved by the Medical Ethics Committee (METC Zuid-West Holland/Erasmus Medical Center; MEC-2020-0812). The results will be published in peer-reviewed academic journals and disseminated to patient organisations and media. - Trial registration number NCT06146725.